FUNGSI SOSIAL PASAR RAKYAT BAGI MASYARAKAT DESA TASIK SERAI BARAT KECAMATAN PINGGIR KABUPATEN BENGKALIS - Bastian, Ahmad; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted by the author to find out what social function of markets for rural communities, Benefits Research The results of this study can be used as additional information, especially studies Sociology as further research similar results could be used as knowledge of the market not only as a single function , The theory is in use in this research is Structural and Functional Social Systems. Kind of research included in qualitative research. Serai DesaTasik research sites in the Western District of Bengkalis Uptown merchants and public research subject Desa Tasik Serai Barat, the data in the data can be primary and secondary data collection techniques of interview, observation and documentation. Functions that are on the market, namely: Socially Religion: friendship and worship together, Social and Cultural: mutual assistance, recreation area, find a mate and where to find information. Socio-economic point of fundraising and as a measure of social status. Social Politics: a campaigning. Concerns expressed in the market, namely: The presence of children selling. The absence of security officers Market.Keywords: FngsiSosial, Social, Religion, social cultural, dan Sosial Politik